Dietary Management for Faecal Microbiota Transplant: An International Survey of Clinical and Research Practice, Knowledge and Attitudes - Clancy, Annabel K.; Gunaratne, Anoja W.; Borody, Thomas J. (Frontiers in Nutrition, 2021)
Faecal microbiota transplantation (FMT) involves homogenisation and infusion of stool from a healthy, highly screened individual into the bowel of an unwell recipient. Dietary intake is an important modulator of the gut microbiota. Currently there are no clinical practice recommendations available to provide patients or stool donors with dietary advice for FMT. This study aimed to conduct an international survey to examine health professionals and researchers’ attitudes, knowledge and current practice recommendations for diet in patients undergoing FMT. An online, cross-sectional, international survey comprising of health professionals and researchers managing patients undergoing treatment with FMT was conducted between July-October 2020. Purposeful and snowball sampling techniques were employed to identify eligible participants who were sent an email invitation and two email reminders with a link to participate in the electronic survey. The survey comprised 21 questions covering demographics, current practice, beliefs and future directions regarding FMT and diet. Closed responses were calculated as proportions of total responses. Open-ended responses were systematically categorised. Common themes were identified from recurring categories.Fifty-eight (M 60%) participants from 14 countries completed the survey. Participants were gastroenterologists (55%), with 1-5 years’ experience working in FMT (48%) and treating up to ten patients with FMT per month (74%). Participants agreed that diet was an important consideration for FMT recipients and stool donors (both 71%), and that it would affect the outcomes of FMT. However, they did not feel confident in providing dietary advice to patients, nor that there was sufficient evidence to provide dietary advice and this was reflected in their practice. Future research must collect information on the dietary intake of patients and donors to better understand the relationship between diet and FMT outcomes. In clinical practice, promotion of healthy eating guidelines aligns with current practice and literature.